A new salamander of the genus Bolitoglossa (Caudata: Plethodontidae) from the highlands of western Panama - Ponce, Marcos; Navarro, Deivy; Morales, Roger; Batista, Abel (Zootaxa, 2022)
We describe a new species of salamander of the genus Bolitoglossa from the Cordillera de Talamanca in western Panama. The new species is distinct from its congeners by its dorsal and ventral coloration, finger and toe webbing, and a comparatively high maxillary teeth count in relation to SVL. Analysis of mitochondrial DNA sequences revealed an isolated phylogenetic position of the new species which is related to the B. robinsoni, B. subpalmata and B. epimela species groups, all four of which form a subclade within the subgenus Eladinea.